2017
DOI: 10.1590/0034-7167-2016-0405
|View full text |Cite
|
Sign up to set email alerts
|

Óbitos fetais e neonatais de filhos de pacientes classificadas com near miss

Abstract: How to cite this article: Nardello DM, Guimarães AMDN, Barreto IDC, Gurgel RQ, Ribeiro ERO, Gois CFL. ABSTRACT Objective: identify the epidemiological aspects of early fetal and neonatal deaths in children of patients classifi ed with near miss and the factors associated with this outcome. Method: a cross-sectional study of 79 women identifi ed with near miss and their newborns. The variables were analyzed using Fisher's exact test. Risk factors were estimated based on unadjusted and adjusted odds ratios, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 21 publications
(41 reference statements)
4
11
0
9
Order By: Relevance
“…A supporting study in Indonesia revealed that survival of newborns from mothers without severe complications was better than that of newborns from mothers with obstetric complications, and studies in Brazil also revealed that maternal near miss were strongly associated with prematurity, neonatal asphyxia, and early respiratory discomfort. 24,25 This finding is also supported by studies from the Jimma University Specialized Hospital and the Dessie Referral Hospital, which showed that obstetric complications during current pregnancy and complications during labor and delivery were strongly associated with adverse birth outcomes (low birth weight, preterm birth, low APGAR score, and still birth). [26][27][28] Referral linkage was found to be significantly associated with NNM in this study, increasing the odds of NNM by three-times compared to mothers who were not referred.…”
Section: Discussionsupporting
confidence: 54%
“…A supporting study in Indonesia revealed that survival of newborns from mothers without severe complications was better than that of newborns from mothers with obstetric complications, and studies in Brazil also revealed that maternal near miss were strongly associated with prematurity, neonatal asphyxia, and early respiratory discomfort. 24,25 This finding is also supported by studies from the Jimma University Specialized Hospital and the Dessie Referral Hospital, which showed that obstetric complications during current pregnancy and complications during labor and delivery were strongly associated with adverse birth outcomes (low birth weight, preterm birth, low APGAR score, and still birth). [26][27][28] Referral linkage was found to be significantly associated with NNM in this study, increasing the odds of NNM by three-times compared to mothers who were not referred.…”
Section: Discussionsupporting
confidence: 54%
“…In the first study performed in 2013, the authors found high frequencies of fetal and neonatal deaths among MNM cases, and the main factors associated with outcomes were severe pre-eclampsia, placental abruption, prematurity and endometritis; there was also an association between laboratory criteria and adverse outcomes [7]. These results were corroborated by a second study that was performed in 2017 [8]. …”
Section: Discussionmentioning
confidence: 87%
“…Two studies investigated the relationship between MNM and adverse perinatal outcomes (fetal and neonatal deaths) [7, 8]. In the first study performed in 2013, the authors found high frequencies of fetal and neonatal deaths among MNM cases, and the main factors associated with outcomes were severe pre-eclampsia, placental abruption, prematurity and endometritis; there was also an association between laboratory criteria and adverse outcomes [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of neonatal deaths are preventable and to reduce these deaths; invest in maternal and neonatal care during childbirth and in the rst 24 h after birth [1,2]. Severe infection, LBW and birth asphyxia were the most common causes of NNM in the health facilities [2,[14][15][16]. Similarly, in Ethiopia, 2015 government report revealed that Preterm birth complications 22%, intra-partum related events 32%, infection 20% and congenital abnormalities 12% were among the leading causes of neonatal death [2,17,18].…”
mentioning
confidence: 99%